Changes in barrier health status of the gill for grass carp (Ctenopharyngodon idella) during valine deficiency: Regulation of tight junction protein transcript, antioxidant status and apoptosis-related gene expression. Issue 2 (August 2015) - Feng, Lin; Luo, Jian-Bo; Jiang, Wei-Dan; Liu, Yang; Wu, Pei; Jiang, Jun; Kuang, Sheng-Yao; Tang, Ling; Zhang, Yong-An; Zhou, Xiao-Qiu
Abstract: This study investigated the effects of dietary valine on tight junction protein transcription, antioxidant status and apoptosis on grass carp gills ( Ctenopharyngodon idella ). Fish were fed six different experimental diets containing graded levels of valine (4.3, 8.0, 10.6, 13.1, 16.7, 19.1 g/kg). The results indicated that valine deficiency decreased Claudin b, Claudin 3, Occludin and ZO-1 transcription and increased Claudin 15 expression in the fish gill ( P  < 0.05). These effects were partly due to the down-regulation of interleukin 10 (IL-10), transforming growth factor β1 (TGF-β1) and IκB α and the up-regulation of relative mRNA expression of interleukin 1β (IL-1β), interleukin 8 (IL-8), tumor necrosis factor-α (TNF-α) and nuclear factor κB P65 (NF-κB P65) (P < 0.05). However, valine deficiency and valine supplementation did not have a significant effect on Claudin c and Claudin 12 expression in grass carp gills ( P  > 0.05). Valine deficiency also disrupted antioxidant status in the gill by decreasing anti-superoxide radicals and hydroxyl radical capacity, glutathione contents and the activities and mRNA levels of Cu/Zn superoxide dismutase (SOD1), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR) and glutathione-S-transferase (GST) ( P  < 0.05). These results may be ascribed to the down-regulation of NF-E2-related factor 2 (Nrf2), target of rapamycin (TOR) and ribosomal protein S6 kinase 1 (S6K1) and the up-regulation of Kelch-like-ECH-associated protein 1 (Keap1) ( P  < 0.05). Additionally, valine deficiency induced DNA fragmentation via the up-regulation of Caspase 3, Caspase 8 and Caspase 9 expressions ( P  < 0.05). These results may be ascribed to the improvement in ROS levels in the fish gill ( P  < 0.05). Taken together, the results showed that valine deficiency impaired the structural integrity of fish gill by disrupted fish antioxidant defenses and regulating the expression of tight junction protein, cytokines, antioxidant enzymes, NF-κB p65, IκBα, TOR, Nrf2, Keap1 and apoptosis-related genes in the fish gill. Highlights: Valine deficiency regulated tight junction proteins transcript abundance. Valine deficiency decreased the antioxidant status. Valine regulated the NF-κB, Nrf2 and TOR signaling pathways. Valine deficiency induced DNA fragmentation. Valine regulated apoptosis-related gene expression.